Phenotypic and Molecular Identification of Cronobacter sakazakii Isolated from Clinical Specimens in Thi-Qar Province - Al-aawadi, Karrar khalaf (University of Thi-Qar Journal of Science, 2022)
Cronobacter sakazakii is a food-born pathogenic bacteria which can cause several diseases for human and animals. The present study focused on the isolation of this species from clinical specimens ( Burn humans, stool of patients with diarrhea, urine with UTI. in addition to hospital environments specimens) from different sexes and ages. The specimens have been taken from group of hospitals in Al-Nasiriyah city (center of Thi-Qar province- south of Iraq). The identification was done by both phenotypical and molecular methods with using of culture (on enriched, selective and differential media), microscopic examination, biochemical tests, API. 20 E. system and PCR. for amplification of ITS. region (the space between 16s and 23s ribosomal DNA.).Out of 400 specimens (100 from each source) there were 16 (4 %) of specimens give positive for C. sakazakii which included: 4/100 burns specimens (4%), 6/100 stool specimens (6%), 0/100 urine (0%) and 6/100 hospital environments specimens (6%). The 16 isolates have been identified by PCR. for the presence of ITS. region with using of SG. Primer (282 bp.), all the 16 (100%) isolates were positive for this gene. This species was exist in the clinical specimens and can cause diarrhea and burn infection in the area of study with ratio equal to what obtain by other researchers. There are variation in results of biochemical tests according to its strains which leads to difficulty with diagnosis, furthermore the diagnosis with ITS. showed the same results of phenotypical methods used in the present study